Evaluation of the effectiveness of functional rehabilitation in patients with multiple sclerosis - Grochala, Agata; Zdziarski , Krzysztof (Journal of Education, Health and Sport, 2022)
Multiple sclerosis is an inflammatory demyelinating disease of the central nervous system. May have individual and dynamic course, with symptoms of varying severity. It takes 4 forms: relapsing-remitting, primary progressive, secondary progressive and relapsing-chronic. Aim of the research: Evaluation of the effectiveness of functional rehabilitation in patients suffering from multiple sclerosis. Material and methods: The research group consisted of 94 people (67 women and 27 men) aged 24-70 years, diagnosed with multiple sclerosis. Study participants went through a four-week process rehabilitation based on functional exercise. In research the survey method was used and the research technique was used proprietary questionnaire. Results: The research confirmed the improvement of physical fitness of patients suffering from multiple sclerosis due to the rehabilitation process. In total, 78.72% of the respondents described their physical condition as better or much better than before rehabilitation. Only a few – 3,19% – considered that rehabilitation did not improve the quality of life. The vast majority of respondents - 70.21% as a result of rehabilitation indicated an improvement in independence in everyday functioning. In 93,62% it influenced a better well-being. Conclusions: A correlation has been demonstrated between the performance of kinesiotherapeutic rehabilitation in patients with multiple sclerosis and the improvement of their physical fitness. A significant difference was found in the degree of satisfaction with one’s own functional state before and after the rehabilitation process.